Wykorzystanie metody porządkowania liniowego do oceny polskiego rynku nieruchomości - Foryś, Iwona (The Classification Analysis for the Estimation of the Polish Property Market, 2008)
The article introduces the classification methods for the estimation of the Polish property market to describe it by the determinants of property market development. The author uses demographic. economic, supplying and instrumental variable. The author uses the synthetic measure of the development to the classification of provinces according to the solid norm. The research includes three years 2003-2005. The results which are obtained let select investment areas, areas deviating from the norm which demand stimulations on the part of local administration.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 381-389